2004
DOI: 10.1007/s00484-004-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Poaceae pollen frequencies and associations with meteorological parameters in Brisbane, Australia: a 5-year record, 1994?1999

Abstract: Grass pollen is an important risk factor for allergic rhinitis and asthma in Australia and is the most prevalent pollen component of the aerospora of Brisbane, accounting for 71.6% of the annual airborne pollen load. A 5-year (June 1994-May 1999) monitoring program shows the grass pollen season to occur during the summer and autumn months (December-April), however the timing of onset and intensity of the season vary from year to year. During the pollen season, Poaceae counts exceeding 30 grains m(-3) were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 29 publications
4
43
2
1
Order By: Relevance
“…Therefore it is important to monitor airborne pollen concentrations in city agglomerations. In recent years, a number of publications have highlighted differences or similarities that exist with pollen in the atmosphere at various locations (Green et al 2004;Emberlin et al 1994;Galan et al 1995).…”
mentioning
confidence: 99%
“…Therefore it is important to monitor airborne pollen concentrations in city agglomerations. In recent years, a number of publications have highlighted differences or similarities that exist with pollen in the atmosphere at various locations (Green et al 2004;Emberlin et al 1994;Galan et al 1995).…”
mentioning
confidence: 99%
“…Other several studies found significant positive correlations between daily Poaceae pollen concentration and daily maximum temperature [31,34], daily mean temperature [35,36], and daily global solar flux [31,34]. Relative humidity and rainfall [35][36][37][38][39][40] had a negative effect. Many studies indicate some meteorological elements related to the start of Poaceae seasons: mean temperature in March-April (in the Netherlands), mean temperature before the season start (in Poland), total rainfall in July (in Australia), rainfall in June (in the Iberian Peninsula), cumulative temperature above 5.5°C in March-April, minimum temperature in the first decade of April and maximum temperature in the second decade of April (in the United Kingdom) [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate some meteorological elements related to the start of Poaceae seasons: mean temperature in March-April (in the Netherlands), mean temperature before the season start (in Poland), total rainfall in July (in Australia), rainfall in June (in the Iberian Peninsula), cumulative temperature above 5.5°C in March-April, minimum temperature in the first decade of April and maximum temperature in the second decade of April (in the United Kingdom) [41][42][43][44][45][46]. Daily maximum temperature (optimum 21-25°C), daily mean temperature and anticyclonic synoptic situation on the day before the forecasted day have been reported as the main variables influencing the daily Poaceae pollen concentration [8,29,39,47,48]. The interpretations of most reports are based on various methods of statistical analysis (Pearson or Spearman correlation, regression analysis, time series analysis, artificial neural networks) [49].…”
Section: Discussionmentioning
confidence: 99%
“…If the maximum delayed temperature (Tmax_r) is greater than 19.8˚C, more pollen will be detected in the aerobiological samples. Many authors establish a positive relationship between pollen concentrations and temperature (Green et al, 2004;Dvorin et al, 2001), while others estimate that a temperature of between 20 -25˚C is ideal for the detection of the greatest pollen concentrations (Andersen, 1991;Emberlin, 1994).…”
Section: Discussionmentioning
confidence: 99%